Teacher Peer Observation and Student Test Scores: Evidence from a Field Experiment in English Secondary Schools - Burgess, Simon; Rawal, Shenila; Taylor, Eric S. (Journal of Labor Economics, 2021)
This paper reports on a field experiment in 82 high schools trialing a low-cost intervention in schools’ operations: teachers working in the same school observed and scored each other’s teaching. Students in treatment schools scored 0.07 student standard deviations higher on math and English exams. Teachers were further randomly assigned to roles—observer and observee—and students of both types benefited, observers’ students perhaps more so. Doubling the number of observations produced no difference in student outcomes. Treatment effects were larger for otherwise low-performing teachers.